The Differences of Average Level Serum N Terminal Prob-Type Natriuretic Peptide (NTPROBNP) in Hypertension Patients with and without Left Ventricular Hypertrophy At Cardiology Outpatients Dr. Sardjito General Hospital Yogyakarta - Gusti Hariadi Maulana; Lucia Krisdinarti; Hariadi Hariawan (Faculty of Medicine Universitas Gadjah Mada, 2015)
Introduction. Hypertension cause changes in the structure and function of cardial as triggers neurohormonal and vascular changes that concentric cardiac hypertrophy. Myocyte volume expansion or increased pressure will trigger the synthesis of pre-proBrain Natriuretic Peptide (BNP) in the ventricular myocardium. Pre-proBNP will be converted into proBNP and proBNP will be converted into the form of BNP and N-terminal proBNP (NT proBNP).Aim. This study aimed to determine differences in BT pro BNP in hypertensive patients without LVH and hypertensive patients with LVH. The study design was cross-sectional in cardiology polyclinic`s outpatient at Dr. Sardjito General Hospital Yogyakarta from August 2009 until the sample number is fulfi lled.Method. To analyze the difference between the two groups of hypertensive patients using the t-test for normal distribution, while for abnormal distribution were analyzed with the Mann-Whitney U test. To analyze the normality of data conducted by Kolmogorov-Smirnov. The differences of two groups of hypertensive patients considered as signifi cant if p < 0.005 with confi dence interval of 95%.Results. The results showed 73 study subjects grouped subjects into 2 groups: hypertensive subjects without LVH (31 subjects) and with LVH (42 subjects) based on echocardiography parameters (IVSD, LVPWd, LVIDd, LVM, and LVMI) consisting of 24 males and 49 females. The baseline characteristics between the study groups of hypertensive subjects with and without LVH did not differ signifi cantly either in age, BMI, blood pressure, duration of hypertention therapeutic characteristics of the use of drugs such as ACEI, ARB, β-blocker, CCB, spironolactone and furosemide. Mean NT proBNP levels in hypertensive group without LVH (46.60 ± 45.51) and hypertention with LVH group (201.60 ±192.30 ng/ml). From the results of the Kolmogrov-Smirnov test result that the data distribution was not normal then used Mann-Whitney U test, obtained a statistically significant differences.Conclusion. There were significant differences in the mean levels of serum NT proBNP in hypertensive patients without LVH and hypertensive patients with LVH.